Unpacking the predominance of case study methodology in South African postgraduate educational research, 1995–2004 - Rule, P; Davey, B; Balfour, RJ (South African Journal of Higher Education, 2011)
The Project Postgraduate Educational Research (PPER) data indicate that case study is the most popular methodology among South African education masters and doctorate students in the period 1995–2004. This article reflects on the reasons for the preference for case study by considering epistemological and contextual factors. It unpacks the links between the methodological choice of case study, on the one hand, and the thematic focus and sectoral location of theses, on the other. While acknowledging the strengths of case study methodology regarding manageability, depth and experiential texture, the article argues that the predominance of case study limits the applicability of research to wider questions of policy and implementation, and thus contributes to the hiddenness of students’ voices in public discourse around education. It suggests ways of enhancing the wider relevance of case studies through multiple case designs, sequential case studies, mixed method designs and synoptic reviews.